Estimating the cost of CO2 mitigation by feed in tariff approach in the Philippines - Bakhtyar, Bardia; Lim, C.H.; Aziz, N.; Azam, Muhammad; Prabhakar, Akhilesh Chandra (Asian Network for Scientific Information, 2015)
The Philippines is located in Southeast Asia characterized by a tropical weather and high level of rain which makes this country as a high potential in generating electricity by hydro-power and wind.Solar potential at this country is one of the highest in the world.All these opportunities help the country to replace clean and green renewable energies instead of fossil sources which will reduce the amount of produced carbon dioxide significantly.This study illustrates the Philippines attempts for encouraging investors for investing in renewable energies.Meanwhile the cost of avoiding carbon by generating electricity by solar panels estimated and compared with the other parts of the world.The conclusion shows despite of all opportunities in the country still cost of avoiding CO2 by using solar panels in the Philippines is higher than average world price.